Pengenalan Bahasa Inggris Melalui Aplikasi Alquran English Translation di TPQ Al-Khurriyah - Saputro, Isnaini Eddy; Ingsaputro, Muhammad Hafiz (Lembaga Publikasi Ilmiah Nusantara, 2025)
The purpose of community service entitled Introduction to English through the Al-Quran English Translation application at the Al-Khurriyah Al-Quran Learning Center (TPQ) is to provide a basic introduction to English vocabulary through the Al-Quran translation application to improve and add insight into English to students in TPQ Al-Khurriyah. The steps taken are to carry out a series of activities to introduce English through the Al-Quran English Translation application to children aged 5-9 years, especially the surahs Alfatiha, Al-Ikhlas, Al-Falaq, and An-Nas, to provide early insight into English while facilitating the reading of the Al-Quran, especially Juz 30 to students in TPQ Al-Khurriyah. The results of community service conclude that based on the results of observations, there is an increase in motivation to speak English in TPQ Al-Khurriyah, which is indicated in memorizing the English Surah Alfatihah.